Simulation: a new learning tool for medicine students - Quintana Villamandos, Begoña (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The main objective of the study is to establish a new teaching strategy in the learning of non-technical skills in medical students through simulation in a real environment. For this purpose, we used a real scenario: the Aeroevacuation Medical Unit (UMAER) located at the Torrejón Air Base (Madrid), where medical students of the Complutense University of Madrid carried out the simulation of air transport of critical patients in a real war environment. The results of the present work show the efficacy of simulation in the learning of non-technical skills in medical students.